Advances in the pharmaceutical treatment options for canine osteoarthritis. (14th March 2022) - Pye, C.; Bruniges, N.; Peffers, M.; Comerford, E.
Abstract : Canine osteoarthritis is a significant cause of pain in many dogs and can therefore compromise animal welfare. As the understanding of the biology and pain mechanisms underpinning osteoarthritis grows, so do the number of treatments available to manage it. Over the last decade, there have been a number of advances in the pharmaceutical treatment options available for dogs with osteoarthritis, as well as an increasing number of clinical trials investigating the efficacy of pre‐existing treatments. This review aims to examine the current evidence behind pharmaceutical treatment options for canine osteoarthritis, including non‐steroidal anti‐inflammatory drugs, piprants, monoclonal antibodies, adjunctive analgesics, structure modifying osteoarthritis drugs and regenerative therapies.